TAMAN NASIONAL DALAM WACANA POLITIK KONSERVASIALAM:STUDIKASUSPENGELOLAAN TAMAN NASIONAL GUNUNG-HALIMUN SALAK - Berry Yogaswara (Jurnal Kependudukan Indonesia, 2009)
This paper describes discourse on National Park management through political-ecology framework, using Gunung Halimun-Salak National Park as a case study. The National Park is an arena of contestation among government, non governmental organization, people surrounding the park and also, scientific institute. I argue that the historical and power relationship among stakeholder of the park is an important factor to be considered on the national park management. I identify three ideological way of thinking, namely conservationist, eco-populist and developmentalist. These three groups exist in the management of national park and raise conflicts of accommodation and negotiation among the stakeholders.Keywords: Political ecology, Discourse analysis, Nature Conservation: Halimun salak Mountain National Parks